Attitudes of clients of Dutch pest controllers towards animal welfare in the management of liminal rodents - Maite AAM van Gerwen; T Bas Rodenburg; Saskia S Arndt; Bastiaan G Meerburg; Franck LB Meijboom (Animal Welfare, 2023)
Rodent control tends to involve methods that cause animal suffering, but little attention has been paid to the animal welfare implications of rodent control. The aim of the current study was to gain insight into the opinions and attitudes of clients of Dutch pest controllers, regarding liminal rodents, rodent control, and rodent welfare. A better understanding of their attitudes may contribute to more ethical rodent management programmes. An online survey among 248 clients of Dutch pest controllers was carried out. Respondents, especially those within the agricultural sector, have a relatively negative attitude towards rats and mice. Respondents in the agricultural subgroup do not consider the welfare of liminal rodents important. They also think that the welfare impact of commonly used control methods is limited, and they have low tolerance levels for the presence of rodents. Respondents from other sectors have a far more positive attitude towards rats and mice, consider their welfare to be of greater importance, have a greater estimation of the welfare impact of control methods and show greater tolerance levels towards rodents. The respondents from the latter subgroup have a similar attitude compared to Dutch pest controllers participating in a previous survey. The findings of the current study firstly provide useful information for the further development and practical implementation of preventive control methods. Secondly, they provide input for a more animal-friendly rodent control and for the development of an assessment framework to support ethical decision-making. Finally, they can be helpful for further research and the communication and co-operation between professional pest controllers and their clients.